Vedic learning and management education. Issue 8 (2nd September 2014) - Sirodom, Kulpatra; R. Loza Adaui, Cristian; Habisch, André; Lenssen, Gilbert; Roosevelt Malloch, Theodore; Nandram, Sharda
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discuss how management education in India can benefit from applying a Vedic Learning style. It argues that transformational learning, a key to transforming mindset, also increases the importance of ethical behavior in management education. Design/methodology/approach – The paper is based on a literature review of Vedic education principles and transformational learning. It focusses on how to apply it in the management education. Findings – It presents an analysis of Vedic Learning, the Indian mindset and the role of transformational learning in Indian management education. While there is a decline in practicing Vedic Learning in India, in fact, it carries a huge potential for all-round development which would transform management education. The paper proposes ingredients for management education following Vedic Learning in terms of philosophy, designing programs, teacher's role, teaching environment and by integrating different types of skills for management. Practical implications – It implies that management education can be designed in a Vedic Learning style for revitalizing practical wisdom for facing the challenges of modern society, both in India and other parts of the world. Originality/value – It strengthens the relevance of the concept of Vedic Learning and shows its similarities with transformational learning.